Knowledge, attitudes and risk perceptions about tuberculosis: US National Health Interview Survey - Marks, S. M. (Int J Tuberc Lung Dis, 2008)
BACKGROUND: Tuberculosis (TB) disproportionately affects the human immunodeficiency virus (HIV) infected, foreign-born, Black, Hispanic, American Indian/Alaska Native, Asian, homeless, incarcerated, alcoholic, diabetic or cancer patients, male, those aged >44 years, smokers and poor persons. METHODS: We present TB knowledge, attitudes and risk perceptions overall and for those experiencing TB disparities from the 2000–2005 US National Health Interview Survey (NHIS). RESULTS: A total of 32% of respondents said TB is curable; 44% correctly recognized that TB is transmitted by air. Persons with less knowledge about TB transmission were aged 18–24 years, alcohol abusers, educated <12 years, Hispanics or males. Persons less likely to say TB is curable were aged 18–44 years, smokers, HIV-tested, uninsured, alcohol abusers or homeless/incarcerated. Only 28% of foreign-born persons from Mexico/Central America/the Caribbean said TB was curable. CONCLUSIONS: Knowledge about TB transmission and curability was low among a representative US population. Renewed TB educational efforts are needed for all populations, but should be targeted to populations disproportionately affected, especially those who are HIV-infected, homeless/incarcerated, Black, alcohol abusers, uninsured or born in Mexico/Central America/the Caribbean.